Implementation and Actualization of Human Resource Development Programs to Improve Teacher Professionalism in Junior High Schools in the Hinterland Area of Batam - Pusvariauwaty Pusvariauwaty; Tubagus Pamungkas; Alpino Susanto (Jurnal Inovasi Pendidikan dan Sains, 2025)
This study explores the implementation and actualization of human resource development (HRD) programs aimed at enhancing teacher professionalism in junior high schools within Batam’s hinterland. The research is driven by the need to address educational disparities in remote areas, particularly concerning teacher competence. Employing a qualitative approach, data were collected through interviews, observations, and document analysis involving principals, teachers, and local education officials. The findings reveal that while HRD initiatives such as training and workshops have been introduced, their implementation faces constraints, including limited funding, inadequate access to training facilities, and minimal post-training support. The actualization of these programs remains suboptimal, with few practical applications in classroom contexts. Teachers often encounter difficulties in applying theoretical knowledge due to insufficient institutional backing. This study concludes that improving teacher professionalism in hinterland areas requires increased access to practical, context-relevant training, enhanced institutional support, and greater stakeholder involvement. The results underscore the importance of aligning HRD strategies with local conditions to foster meaningful and sustainable professional growth among educators. Implications suggest the need for policy reforms and targeted investment to optimize HRD outcomes in remote educational settings